2016
DOI: 10.1021/acs.analchem.6b04024
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Organic Molecules on the Basis of a Poly(N-isopropylacrylamide) Microassembly Formed by Plasmonic Optical Trapping

Abstract: We demonstrate that a poly(N-isopropylacrylamide) (PNIPAM) microassembly, formed by plasmonic optical trapping, can provide the platform for a highly sensitive detection technique for fluorescent and nonfluorescent organic molecules dissolved in aqueous solution. PNIPAM microassemblies can be easily formed by a combination with a photothermal effect and an enhanced optical force. These physical phenomena were obtained through resonant excitation of localized surface plasmon (LSP). Sparsely distributed fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Details of our plasmonic optical trapping system combined with fluorescence microspectroscopy have been described elsewhere and in the Supporting Information (Fig. S1) 33,34,55 , and are briefly introduced here. We used a cw near-infrared (NIR) laser (λ = 808 nm) for LSP excitation and cw near-ultraviolet and visible lasers (λ = 375, 473 nm) for fluorescence excitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of our plasmonic optical trapping system combined with fluorescence microspectroscopy have been described elsewhere and in the Supporting Information (Fig. S1) 33,34,55 , and are briefly introduced here. We used a cw near-infrared (NIR) laser (λ = 808 nm) for LSP excitation and cw near-ultraviolet and visible lasers (λ = 375, 473 nm) for fluorescence excitation.…”
Section: Methodsmentioning
confidence: 99%
“…Following early demonstrations, POT has undergone rapid growth, and has been used to trap various nanomaterials such as polymer beads 10,[19][20][21][22][23][24][25][26][27] , metallic nanoparticles 12,18 , quantum dots 13,28,29 , dye aggregates 30,31 , and so on. In addition to these hard nanospheres, we have demonstrated that POT is also applicable to soft materials such as flexible polymer chains homogeneously dissolved in water 32,33 .…”
mentioning
confidence: 99%
“…We successfully obtained the Raman spectrum of a single particle. Figure 3b shows the Raman spectrum in the high-wavenumber region (2800-3800 cm −1 ) corresponding to the CH stretching modes of the PNIPAM main chain [53,54] Poly(ethylene oxide) [55] Poly(N-isopropylacrylamide) and its derivatives [38,40,56,57] Poly(vinyl methyl ether) [39] Polyfluorene [58,59] (2800-3050 cm −1 ) and those of the OH stretching modes (3100-3800 cm −1 ). With increasing near-infrared laser power, the Raman scattering intensity of the CH stretching modes increased because of the increasing PNIPAM concentration in the microparticle.…”
Section: Optical Tweezers For Pnipam Combined With Confocal Raman Micmentioning
confidence: 99%
“…We have demonstrated plasmonic optical tweezers for nanoparticles such as quantum dots [66], polystyrene nanospheres [67,68], J-/H-aggregates [69], DNA [70,71], and polymer chains [72]. Furthermore, we applied POT of PNIPAM for molecular condensation and microspectroscopic detection, as described in the next section [40]. In comparison with conventional optical tweezers, POT has three advantages ( Fig.…”
Section: Plasmonic Optical Tweezersmentioning
confidence: 99%
See 1 more Smart Citation